2020
DOI: 10.1177/0269215519901153
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a patient-directed activity program on functional outcomes and activity participation after stroke during inpatient rehabilitation—a randomized controlled trial

Abstract: Objective: Individuals post stroke are inactive, even during rehabilitation, contributing to ongoing disability and risk of secondary health conditions. Our aims were to (1) conduct a randomized controlled trial to examine the efficacy of a “Patient-Directed Activity Program” on functional outcomes in people post stroke during inpatient rehabilitation and (2) examine differences three months post inpatient rehabilitation discharge. Design: Randomized control trial. Setting: Inpatient rehabilitation facility. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Reapplication of eligibility to full texts resulted in 20 selected trials for review [ 7 , 40–58 ]. One of the 20 selected trials [ 52 ] was identified by checking reference lists or citation tracking ( Figure 1 ). Agreement between reviewers was fair for initial screening of titles and abstracts ( κ = 0.336, 95%CI 0.261–0.411) and substantial for screening full texts ( κ = 0.704, 95%CI 0.534–0.874).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reapplication of eligibility to full texts resulted in 20 selected trials for review [ 7 , 40–58 ]. One of the 20 selected trials [ 52 ] was identified by checking reference lists or citation tracking ( Figure 1 ). Agreement between reviewers was fair for initial screening of titles and abstracts ( κ = 0.336, 95%CI 0.261–0.411) and substantial for screening full texts ( κ = 0.704, 95%CI 0.534–0.874).…”
Section: Resultsmentioning
confidence: 99%
“…The most common primary diagnosis was stroke ( n = 4 trials). Fourteen trials were in acute wards ( n = 10 surgical, n = 3 medical, n = 1 mixed medical/surgical) [ 41–43 , 45–48 , 50 , 51 , 53–57 ] and six trials in rehabilitation wards [ 7 , 40 , 44 , 49 , 52 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dessa forma e apesar da escassez de literatura acerca do tema sobre como funciona o trabalho das equipes inter e multidisciplinares, é notória a possibilidade de realização do trabalho em equipe no atendimento a vítimas de AVC. Também é evidente a importância do entendimento das possíveis formas de trabalho desses grupos e quem são os profissionais envolvidos, pois, as equipes são sistemas ativos de aprendizagem, nos quais os indivíduos desenvolvem relacionamentos e aplicam o conhecimento para resolver problemas relacionados aos pacientes internados, entre eles, os que são acometidos por um AVC (Schiavi et al, 2018;Amatangelo et al, 2020;Schwarzbach et al, 2020;Swank, 2020).…”
Section: Discussionunclassified